Is executive attention affected by environmental lighting conditions? - Nino Wessolowski; Raschida Jasmin Rahim (PLoS ONE, 2025)
Bright daylight has various positive influences, such as the long-term synchronization of circadian rhythms and an associated alertness that creates optimal conditions for attentional performance. However, the short-term effects of light on attention have not yet been sufficiently researched. Studies of these short-term effects on selective attention also showed partly contradictory effects. To investigate these short-term effects, 95 participants completed the Attention Network Test, under conditions of bright daylight or warm-white light. The focus of the present study was on executive attention, because this construct comes closest to the ANT short form of selective attention used. A significant enhancement of executive attention was observed under bright daylight conditions. This specifically means a short term effect of bright daylight on executive attention and thus selective attention in young adults.